First evaluation of an index of low vagally-mediated heart rate variability as a marker of health risks in human adults: proof of concept - Jarczok, Marc N.; Koenig, Julian; Wittling, Ralf Arne; Fischer, Joachim E.; Thayer, Julian F. (Journal of Clinical Medicine, 2019)
Multiple studies have demonstrated low vagally-mediated heart rate variability (HRV) being associated with a range of risk factors for heart disease and stroke, including inflammation, hyperglycemia, hyperlipidemia, and hypertension. Yet, no cut point exists that indicates elevated risk. In the present study we sought to identify a cut point-value for HRV that is associated with elevated risk across a range of known risk factors. Methods: A total of 9550 working adults from 19 study sites took part in a health assessment that included measures of inflammation, hyperglycemia, hyperlipidemia, and hypertension and vagally-mediated HRV (Root mean square of successive differences between normal heartbeats (RMSSD)). Multiple age and sex adjusted logistic regressions were calculated per risk factor (normal versus clinical range), with RMSSD being entered in binary at different cut points ranging from 15-39 msec with a 2 msec increment. Results: For daytime RMSSD, values below 25 +/- 4 indicated elevated risk (odds ratios (OR) 1.5-3.5 across risk factors). For nighttime RMSSD, values below 29 +/- 4 indicated elevated risk (OR 1.2-2.0). Conclusion: These results provide the first evidence that a single value of RMSSD may be associated with elevated risk across a range of established cardiovascular risk factors and may present an easy to assess novel marker of cardiovascular risk.
Gesehen am 14.04.2020